Potencial tecnológico e nutricional de subprodutos do processamento de frutas - Macagnan, Fernanda Teixeira (2013)
The passion fruit peel (CM), apple pomace (BM) and orange bagasse (BL) are by-products generated in large quantities and usually wasted by brazilian industries of juices processing. However have nutritional qualities important for health, as relevant levels of dietary fiber. In this context, the study aimed to characterize the flour of these by-products, study potential nutritional as alternative sources of fiber in diets drawn up for rats, and test the nutritional and sensory quality of honey breads enriched with these flours. In step characterization, it was verified a high content of dietary fiber, which varied 54.82 to 76.84% in dry matter (DM), highlighting the soluble fraction (18.97% to 25.17% in DM), mainly composed of pectin (49.19% to 91.25% of the soluble fiber). Phenolic compounds were also elevated in the samples analyzed (479.71 to 862.11 mg% in DM). The BM stood out for higher fiber content, pectin, condensed tannins and greatest copper binding capacity. The CM presented a high mineral content, very small percentage of fat, high hydration capacity and greater fat binding capacity. The BL was the by-product with higher levels of soluble fiber and phenolic content. In biological assay, conducted for 40 days, it was used 32 male Wistar rats, with 21 days old, randomly distributed (eight animals / treatment) between the following experimental treatments: TC, control treatment with cellulose as a fiber source; TBM; treatment with apple pomace as fiber source; TBL, treatment with orange bagasse as a source of fiber; TCM; treatment with passion fruit peel as a source of fiber.The different sources of fiber did not affect the average consumption, weight gain, feed conversion, gastrointestinal transit time, and neither exerted influence on the weight of the intestine empty, kidney, liver and epididymal fat of animals. There was also not significant difference in the levels of total cholesterol, HDL cholesterol, albumin, total protein and lipids in the liver. However, it was found that the addition of these by-products has enabled significant reductions in serum triglycerides and hepatic cholesterol, and also promote changes in important parameters for gut health (pH, nitrogen and fecal moisture) and play important roles in the control of postprandial glycemia. The fiber derived from BM showed greater potential to reduce the absorption and metabolization of fat for its increased excretion in feces, but it was the only one that did not exercise significant influence on fasting glucose. The fiber from the CM had higher apparent digestibility and the animals fed with BL showed the better postprandial glycemic response. The replacement of 15% of wheat flour standard formulation of honey bread by flours fruit by-products of allowed the reduction of caloric value and the increase in dietary fiber content (from 6.62 to 9.61% in DM to the formulations added BL and BM, respectively) and your soluble fraction. Sensory evaluation of honey breads enriched with flour by-products indicated good acceptability average for all parameters evaluated (color, aroma, flavor, texture, overall acceptability) and favorable purchase intent of these products. Is founded, thus, the rational utilization of these by-products of processing fruits as alternative sources of fiber with potential nutritional and technological to be used in human food.